GERAKAN MASYARAKAT HIDUP SEHAT (GERMAS) “AYO MAKAN BUAH DAN SAYUR” PADA SISWA SMAN 1 TELUKJAMBE TIMUR KARAWANG - Risma Rahmatunisa; Ratih Kurniasari; Eka Andriani (JURNAL CEMERLANG : Pengabdian pada Masyarakat, 2019)
Fruits and vegetables consumption are important for our health but its consumption is low especially for teeneger. High school student are the vulnerable age group for consumption of fruits and vegetables. Their eating habits will give the impact for their growth, development and health in the future. SMAN 1 Telukjambe students tend to eat fast food and rarely consume fruits and vegetables. The purpose of this activity is to motivate and increase the awareness and comsumption of fruits and vegetables of the participants. The method used in this activity was counseling using food model and questionnaire on pretest and posttest with category of knowledge, preference, and consumption of 28 students SMAN 1 Telukjambe Timur. The result of this activity will be descriptive analysis. The result showed that after counseling, students knowledge about fruits and vegetables were increase by amount 80%. Students preference of fruits were 92% positive and students preference of vegetables were 79% positive. But in contrast, their consumption just 4% for fruits and 25% for vegetables. So, it is expected to increased students awareness and students consumption of fruits and vegetables after this activity.